Development of an in vitro triculture model of intestine inflammation to assess the immunomodulatory properties of cassava and roselle, two African green leafy vegetables - Fioroni, Nelly; Ponce de León Rodríguez, Maria Del Carmen; Leconte, Nicolas; Mouquet-Rivier, Claire; Guzman, Caroline; Boudard, Frédéric; Dhuique-Mayer, Claudie; Collin, Myriam; Deglos, Anaïs; Reboul, Emmanuelle; Bravo-Núñez, Ángela; Laurent-Babot, Caroline (NFS journal, 2025)
The intestine integrity and function are crucial for nutrient absorption and to prevent the entry of harmful antigens. In sub-Saharan Africa, frequent infections and enteric dysfunction can cause intestinal inflammation that is associated with stunting. Therefore, to study the anti-inflammatory effects of cassava and roselle leaves, commonly consumed as sauces, we developed an in vitro triculture model of intestine inflammation using intestinal Caco-2 (colorectal adenocarcinoma) and HT29-MTX (goblet cell-like) together with the macrophage-like THP-1 cells. Stimulation of this model with lipopolysaccharide/interferon-γ resulted in mucus over-production, higher pro-inflammatory cytokine release and loss of intestinal barrier integrity due to increased permeability. Polar/non-polar extracts and digested sauces from cassava and roselle leaves reduced cytokine production in both intestinal and THP-1 cells to different extents and restored barrier integrity and permeability. The developed and validated triculture model of inflamed intestine thus demonstrated the anti-inflammatory properties of cassava and roselle leaves, despite moderate responses. [Display omitted]